Grupos - Colella, Olga. (Buenos Aires : Sigmar, 1994)
Photographs explore how things are alike and different.
Titulo original: My first look at sorting.
"Un libro Dorling Kindersley" -- T.p. verso.
Keywords: Grupos -- Literatura juvenil; Set theory -- Juvenile literature; Spanish language materials